Pre-and postpartum levels of childbirth fear and the relationship to birth outcomes in a cohort of Australian women - Fenwick, Jennifer; Gamble, J.; Nathan, E.; Bayes, Sara; Hauck, Yvonne (Blackwell Publishing, 2009)
To investigate pre- and postpartum levels of childbirth fear in a cohort of childbearing women and explore the relationship to birth outcomes.While results are mixed, there is evidence that fear of childbirth is associated with mode of birth. Limited theoretical work around childbirth fear has been undertaken with Australian women.Women (n = 401) completed the Wijma Delivery Expectancy/ Experience Questionnaire (W-DEQ) version A at 36 weeks gestation, with 243 (61%) women also completing version B at six weeks postpartum. Scores were summarised with means and standard deviations. Content analysis of the free statements identified nine issues of concern. Twenty-six percent of pregnant women reported low levels of childbirth fear, 48% were moderately fearful and 26% were highly fearful. Fear decreased after birth for those women in the high antenatal fear group, however surgical intervention at birth and suspected fetal compromise increased levels of postpartum fear. Univariately, high antenatal fear was associated with emergency caesarean delivery, however after adjustment for nulliparity and fetal compromise the association disappeared. Australian-born women were more likely to report higher levels of fear and experience higher rates of caesarean section than participants of non Australian origin.Results support those from earlier studies in showing that nulliparous women experience more fear than parous women before birth and that there is no difference in levels of postpartum fear between these two groups. Fear levels were high in Australian women when compared to a Swedish sample.